The Significance of Emotional Intelligence Across Various Professions - Avlayev Orif Umirovich (Next Scientists International Journal EIJP, 2026)
This article examines the role of emotional intelligence (EQ) in the modern labor market and its impact on efficiency across various professional fields. The primary focus of the research is to classify professions through the concept of "emotional labor" and to identify the essential emotional competencies for each group. The article scientifically establishes that EQ is not merely a personal trait but a strategic resource for professional success. Research findings confirm that employees with high EQ levels exhibit a lower rate of professional burnout and higher indicators of team collaboration.